The principles of article ethics and policy applied to classroom daily: some points. - Araújo, Adão Alves (Faculdade de Filosofia e Ciências, 2019)
This article aims to discuss in a reflexive way some concepts of the ethics and politics of Aristotle, with a view to its application in the school, by teachers, aiming the learning and development of the virtues proposed by the philosopher, who Are the pillars of good coexistence and justice between students and teachers, with the fundamental pillar of friendship between individuals, both teachers and students, as well as among themselves, and, among teachers, aiming at a greater good: the development and The improvement of ethical and political virtues. From the exercise of freedom and friendship, grounded in justice, good community socializing in the pursuit of better conditions for the exercise of learning, study, moral virtues and affectivity between teachers and students. In no way does it suggest the resolution of all the difficulties and failures of education. It Reflects on possible, imaginable and achievable alternatives that contribute in order to add options and choice for the improvement and development of friendship for good relationship in everyday life, school and classroom, so Worn out by policies of isolation and distancing from the elements of friendship and justice, present in daily life, caused by the most varied discourses and educational policies, products of successive attempts over time. Submission: 2019-03-30